Peran Media Sosial Instagram Terhadap Minat Berwirausaha Mahasiswa - Hazizah, Siti Nur; Padli Nasution, Muhammad Irwan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research was conducted to determine the role of social media Instagram on student entrepreneurship interest. This study uses a combination research method (mixed method), namely a combination of qualitative and quantitative research methods. The type of combination research used is Sequential Exploratory Design, namely in the early stages of research using qualitative methods and the next stage using quantitative methods. The quantitative method will be carried out with an average score. The results and conclusions in this study are: 1. The average score of the Instagram social media role indicator on entrepreneurial interest obtained is 388.08. This shows that the role of Instagram social media is high in growing interest in entrepreneurship for FEBI Uinsu students. 2. The average score of the indicator of interest in entrepreneurship is 387.8. This shows that the category is in the high range, this illustrates that on average the indicators of interest in entrepreneurship in FEBI Uinsu students are high.3. The obstacle in using Instagram social media is that not all features in Instagram are used for entrepreneurship. The obstacle faced in this interest in entrepreneurship is that sometimes the individual does not dig deeper so that when faced with the ups and downs of sales, the individual is not ready to face it.”